Studies on application of scissor-jack braced viscous damper system in wind turbines under seismic and wind loads. (1st October 2019) - Zhao, Zhi; Dai, Kaoshan; Lalonde, Eric R.; Meng, Jiayao; Li, Bowei; Ding, Zhibin; Bitsuamlak, Girma
Highlights: A viscous damper system is proposed for wind turbine vibration control. A simplified aerodynamic damping model is designed for finite element modeling. The combination of surrogate and multi-objective optimization methods are adopted. Abstract: With the rapid development of the wind energy industry many wind farms have been constructed in regions prone to earthquakes and strong winds, which sometimes cause serious structural vibration problems for wind turbines. This paper details the development of a scissor-jack braced viscous damper system (VD-SJB) to suppress excessive vibration of the wind turbine tower. This system can be installed inside the tubular steel tower and is a suitable technology to enhance the structural performance of existing wind turbines. A detailed finite element wind turbine model was built and two damper systems with and without SJB were modelled and compared. Ground motions and strong lateral winds were applied as external loads to operational and parked turbines, respectively. Parameter optimization was performed by building a surrogate model using an artificial neural network and a multi-objective genetic algorithm. The resulting Pareto sets were discussed and the optimal system was evaluated to demonstrate the effectiveness of VD-SJB. Results show that both viscous dampers installed vertically and VD-SJB are able to reduce structural vibrations under seismic or wind conditions. However, VD-SJB is capable of magnifying the stroke of the damper and decrease the damping force, thus it is a more practical solution.